ANALISIS KESULITAN BELAJAR MATEMATIS PESERTA DIDIK TINGKAT SMP PADA PEMBELAJARAN MATEMATIKA - Hakim, Lukman; Rahmi, Depriwana; Yuniati, Suci; Kurniati, Annisah (Universitas Tanjungpura, 2024)
Mathematical learning difficulties are difficulties experienced by a student which refer to the ability to understand, learn and master concepts in mathematics. A student's lack of understanding of mathematical concepts will certainly be a factor that causes their grades to be low. Therefore, appropriate treatment is needed for these children so that they can get more satisfactory grades. The aim of this research is to analyze the level of mathematical learning difficulties experienced by class VII SMP students in mathematics subjects. The method that the author applies is qualitative research with descriptive methods and data collection techniques in the form of questionnaires. The data analysis used is in the form of descriptive percentages where the data will be analyzed in percentage form. The results of the analysis show that the percentage of students' mathematical learning difficulties in this class when viewed from each indicator is in the low criteria. The level of mathematical learning difficulties experienced by students at this school has improved. There are various ways to reduce the level of difficulty in students' mathematical learning, one of which is by designing varied, effective and inclusive learning strategies, so that every child can understand and master mathematical concepts. That way, students' level of mathematical learning difficulties will be resolved